Importance of Nurse Workload Management as the Main Factor Affecting a Patient Safety Culture - Selamat; Indrawati, Ratna; Tahjoo, Anastina (International Journal of Nursing and Health Services (IJNHS), 2022)
Introduction: The implementation of patient safety goals is the compliance behavior of health workers in implementing the standards and targets set by the hospital concerning international patient safety goals to ensure safe services for every patient. The international patient safety goals adopted by the hospital accreditation committee (KARS) have 6 (six) goals. Objective: The purpose of the study was to obtain empirical evidence of the effect of knowledge and workload on the implementation of patient safety goals mediated by patient safety culture. Method: This type of research is a causative quantitative analytic study with a cross-sectional research design. The sample population of this study is 140 nurses with a saturated sampling technique. In this study, measurements are done on primary data in a questionnaire distributed by Google Form to 140 respondents, and all respondents filled out the Google Form. In this study, the analysis was carried out using path analysis. Results: The results showed that knowledge, workload, and patient safety culture simultaneously had a positive and significant effect on implementing patient safety goals. The research findings show that patient safety culture can mediate patient safety goals. The workload does not directly influence the performance of patient safety goals. Recommendations: for hospital management to be more attentive to nursing workload management, the main factor affected patient safety culture. For further research, data from other hospital stakeholders can be added